Mexctenapseudes boeschi, a new tanaidacean genus and species (Crustacea: Peracarida: Apseudomorpha: Parapseudidae) from the Mexican coast of Campeche with the designation of a new related Australian genus to receive Longiflagrum caeruleus (Boesch, 1973) - Drumm, David T.; Heard, Richard W. (Zootaxa, 2022)
Two new genera of parapseudid Tanaidacea belonging to the Discapseudes-Halmyrapseudes Complex sensu Heard et al. (=Complex) are designated from Mexican and Australian waters. Mexctenapseudes boeschi n. gen., n. sp. is described from Campeche Mexico and Pseudolongiflagrum n. gen. is designated from Australia. The new Mexican genus displays similarities to the West Pacific and Indian Ocean genera Ctenapseudes Bamber, Ariyananda & Silva, 1997 and Longiflagrum Guţu, 1995. The new related genus, Pseudolongiflagrum, having affinities with Ctenapseudes and Mexctenapseudes n. gen., is designated to receive Longiflagrum caeruleus (Boesch) known from Australia. A key to the genera within the parapseudid subfamily Parapseudinae Guţu is presented and possible factors concerning the ecology, origins, and distribution of the members of the Complex considered.